Exciton binding energy in bulk MoS2: A reassessment - Saigal, Nihit; Sugunakar, Vasam; Ghosh, Sandip (Applied physics letters, 2016)
Transmittance and photocurrent (PC) spectroscopy has been used to study absorption in bulk 2H-MoS2 at energies close to its direct bandgap at the K-point of the Brillouin zone. Spectral lineshape analysis using the hydrogenic exciton model, together with temperature dependence of absorption and PC spectrum, and also bias dependence of PC, suggests that the feature previously identified as the n = 2 excited state transition of the A exciton, and used to estimate its binding energy E b , has a different origin. The feature is reproduced in simulations only after including the recently identified H-point exciton transition. A consistent picture, which explains E b in terms of other experimentally and theoretically determined parameters, emerges when excitons in bulk MoS2 are considered as quasi 2-dimensional with E b ∼ 84